2022
DOI: 10.3390/foods11121792
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-I-Converting Enzyme Inhibitory Activity of Protein Hydrolysates Generated from the Macroalga Laminaria digitata (Hudson) JV Lamouroux 1813

Abstract: Seaweeds have a long history of use as both food and medicine, especially in Asian cultures. Moreover, there is growing interest in the use of seaweed ingredients and bioactive compounds in pharmaceutical and nutraceutical products. One ailment that seaweed bioactive compounds may impact is hypertension caused by the enzyme Angiotensin Converting Enzyme 1 (ACE-1; EC 3.4.15.1), found within the Renin-Angiotensin Aldosterone System (RAAS), which causes vasoconstriction of blood vessels, including veins and arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 67 publications
1
17
0
Order By: Relevance
“…As for the conditionally essential amino acids, there was no substantial difference in their content between F5, F4, F3, and F2, but all these fractions had higher levels of these amino acids compared to F1 and the full hydrolysate. In a study conducted by Purcell et al [ 47 ], it was reported that the sum of conditionally essential amino acids obtained from Laminaria digitata decreased from 2.7 g/100 g DW to 1.5 g/100 g DW after passing through an ultrafiltration unit with the molecular weight cut off 3 kDa. This depletion of some amino acids could be due to the inability of some peptides containing them to have a molecular weight higher than the filter cut-off [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…As for the conditionally essential amino acids, there was no substantial difference in their content between F5, F4, F3, and F2, but all these fractions had higher levels of these amino acids compared to F1 and the full hydrolysate. In a study conducted by Purcell et al [ 47 ], it was reported that the sum of conditionally essential amino acids obtained from Laminaria digitata decreased from 2.7 g/100 g DW to 1.5 g/100 g DW after passing through an ultrafiltration unit with the molecular weight cut off 3 kDa. This depletion of some amino acids could be due to the inability of some peptides containing them to have a molecular weight higher than the filter cut-off [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ACE-1 inhibitory activity of the 3-kDa permeate fraction generated from Nannochloropsis sp. protein treated with xylanase was determined using the ACE-1 inhibition colorimetric method as described previously [ 38 ]. The permeate fraction inhibited ACE-1 by 96.6% when assayed at a concentration of 1 mg/mL compared to the positive control Captopril ® which inhibited ACE-1 by 99.3% when tested at a concentration of 0.5 mg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…The ACE-1 IC 50 value for IGNNPAKGGLF was 174.4 µg/mL (0.161 µM) ACE-1. Peptide YIGNNPAKGGLF had an IC 50 value of 133.1 µg/mL (0.11 µM) compared to Captopril© with a documented ACE-1 IC 50 value of 500 µg/mL (2.3 µM) [ 8 ]. Previous studies on marine cryptides, used Captopril© as a positive control with IC 50 values of (1.79–15.1 nM) for ACE-1, and another drug Losartan was used as a negative control for ACE-II inhibition, and had IC 50 values of (17.13–146 μM) [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Protein extraction and peptide enrichment using molecular weight cut-off (MWCO) filtration was performed prior to MS characterisation in accordance with the method outlined in [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation